Decision support evaluation for building information modeling software selection - Nursal, Ahmad Taufik; Omar, Mohd Faizal; Mohd Nawi, Mohd Nasrun (Penerbit UTM Press, 2015)
Building Information Modeling (BIM) has shift the construction industry into a new approach in development of project.The effectiveness of BIM towards increasing productivity and quality of project has been reported not only in literature yet project report.Thus, there are numerous of BIM software available with different features and function.This trend has created decision problem among the companies to select the best software that fulfill company need and project needs.Hence, a web-based Decision Support System (DSS) application namely topsis4BIM has been developed.This paper presented the evaluation the proposed DSS though using the latest technology such as web 2.0 and cloud technology.